THE ROLE OF INTELLECTUAL TECHNOLOGIES AND TACTICAL MODELING IN ENSURING STATE BORDER SECURITY (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the issues of transforming the state border security system in the modern geopolitical context. The possibilities of applying artificial intelligence (AI), autonomous sensor networks, and tactical modeling methods in the operational command and control echelons of border troops are scientifically and theoretically substantiated. Furthermore, the prospects for implementing intellectual platforms in the state border protection system of the Republic of Uzbekistan are examined.
Keywords: State border, national security, artificial intelligence, Big Data, asymmetric threats, cognitive management, unmanned aerial vehicles (UAVs), border monitoring.